Efektywność w zarządzaniu kapitałem intelektualnym na przykładzie wybranych sektorów: Efficiency in intellectual capital management based on selected sectors - Skowron, Paweł (Management and Administration Journal, 2021)
This paper presents a method for measuring the value of intangible assets in selected companies listed on the Warsaw Stock Exchange which belong to two sectors: fuel and automotive industries. In this study author identifies how intangibles create added value for the organization. For that purpose the two indicators being used for estimating intangible assets, are: VAIC (Value Added Intellectual Coefficient) - the intellectual indicator of the value added and the q-Tobina indicator. Based on available information included in financial statements of examined enterprises the author made analysis for forming these indicators in the years 2007-2011.